Aging Well for Indigenous Peoples: A Scoping Review - Quigley, Rachel; Russell, Sarah G.; Larkins, Sarah; Taylor, Sean; Sagigi, Betty; Strivens, Edward; Redman-MacLaren, Michelle (Frontiers in Public Health, 2022)
As life expectancy increases for Indigenous populations, so does the number of older adults with complex, chronic health conditions and age-related geriatric syndromes. Many of these conditions are associated with modifiable lifestyle factors that, if addressed, may improve the health and wellbeing of Indigenous peoples as they age. If models of healthy ageing are to be promoted within health services, a clearer understanding of what ageing well means for Indigenous peoples is needed. Indigenous peoples hold a holistic worldview of health and ageing that likely differs from Western models. The aims of this review were to: investigate the literature that exists and where the gaps are, on ageing well for Indigenous peoples; assess the quality of the existing literature on Indigenous ageing; identify the domains of ageing well for Indigenous peoples; and identify the enablers and barriers to ageing well for Indigenous peoples. A systematic search of online databases, book chapters, grey literature, and websites identified 32 eligible publications on Indigenous ageing. Reflexive thematic analysis identified four major themes on ageing well: 1) achieving holistic health and wellbeing; 2) maintaining connections; 3) revealing resilience, humour, and a positive attitude; and 4) facing the challenges. Findings revealed that ageing well is a holistic concept enabled by spiritual, physical, and mental wellbeing and where reliance on connections to person, place, and culture is central. Participants who demonstrated ageing well took personal responsibility, adapted to change, took a positive attitude to life, and showed resilience. Conversely, barriers to ageing well arose from the social determinants of health, such as lack of access to housing, transport, and adequate nutrition. Furthermore, the impacts of colonisation such as loss of language and culture and ongoing grief and trauma all challenged the ability to age well. Knowing what ageing well means for Indigenous communities can facilitate health services to provide culturally appropriate and effective care.